Penerapan Sistem Keselamatan Dan Kesehatan Kerja (K3) Di PT Perkebunan Nusantara I Regional 7 Pagar Alam Sumatera Selatan - Intan Novitri; Panisean Nasoetion; Sulastri Sulastri (Universitas PGRI Palembang, 2025)
Occupational Safety and Health (OHS) is an important component in the operational activities of the plantation and agricultural processing industries because every operational activity has potential risks that require appropriate control. The purpose of this study is to examine the implementation of OHS at PT. Perkebunan Nusantara I Regional 7 Kebun Pagar Alam, South Sumatra in order to obtain an overview of the implementation of the OHS system implemented by the company and to understand the efforts made in creating a safe and structured work environment. Data collection methods were carried out through direct observation in the plantation and factory areas, interviews with workers and management, and review of documents related to OHS policies. The results of the study indicate that the company has implemented an OHS system, such as the use of personal protective equipment (PPE), provision of safety facilities, SOPs, an adequate work environment, and regular training for employees. However, there is still non-compliance by some workers in the use of PPE so that supervision and strengthening of the OHS culture are needed.